Value Estimation Of California Bearing Ratio From Hand Cone Penetrometer Test For Pekanbaru Soils - Soewignjo Agus Nugroho; Muhammad Yusa; Syawal Satibi (Institut Teknologi Bandung, 2019)
In practice, the design of pavement is commonly based on the California Bearing Ratio (CBR) test. This research was performed to study local correlation between Hand Cone Penetrometer (HCP) tests to the field CBR value. The local correlation is determined based on comparisons of HCP and CBR test results for the same density of soil taken from several locations in Pekanbaru City, Indonesia. It was found that there is an approximate linear relation in log scale between HCP test results to CBR values for a certain density of soil. Correlation for HCP and density to CBR has been put forward for the local correlation between the two values. Verification of the formula shows that the correlation can be used relatively accurately for predicting the field CBR values from the HCP test for inorganic soils. For organic soil, the formula need to be further researched.Pada praktiknya, perancangan perkerasan jalan didasarkan pada tes California Bearing Ratio (CBR). Studi ini dilakukan untuk mengetahui korelasi lokal antara tes Hand Cone Penetrometer (HCP) dan tes CBR untuk tanah dengan berat jenis yang sama, yang diambil pada beberapa titik di kota Pekanbaru, Indonesia. Berdasarkan analisis, diketahui bahwa terdapat hubungan linear, dalam skala log, antara nilai tes HCP dan CBR untuk tanah dengan berat jenis tertentu. Studi ini kemudian mendefinisikan persamaan korelasi dari HCP dan berat jenis terhadap CBR untuk korelasi lokal antara nilai HCP dan CBR. Dari hasil verifikasi persamaan, diketahui bahwa persamaan korelasi tersebut cukup akurat dan dapat digunakan untuk memprediksi nilai CBR lapangan dengan menggunakan nilai tes HCP untuk tanah inorganik. Penelitian lebih lanjut perlu dilakukan untuk mendefinisikan formula korelasi untuk tanah organic.